Implementation of the Smart School Awards (SSA) Program Management in Improving the Quality of Education in Secondary Schools - Ridwanulloh, M. Ubaidillah; Vitriani, Laily; Wahyu, Hesti Afrilia Dwi; Arum, Sevi Wulan; Surur, Agus Miftakus; Eko Prasetiyo, Andika (Journal of Islamic Education Students (JIES), 2025)
This study aims to analyze school management strategies in enhancing educational quality through participation in the 2023 Smart School Awards (SSA) at SMP Ar Rahman. Utilizing a descriptive qualitative approach, data were collected through observations, interviews, and document analysis. The data sources included the school principal, teacher representatives, students, and parents. The findings indicate that structured and collaborative school management significantly contributed to the school's success in obtaining the 2023 Smart School Award in the Healthy and Safe School category. These results underscore the importance of effective leadership and collective stakeholder engagement in improving educational quality through performance-based school award programs.┬á┬á